The Use of Receivables as Collateral in Business Practices in Indonesia - Rio Christiawan (Yuridika, 2021)
This article discusses the enforceability of article 9 of Law No 42 of 1999 on Fiduciary Guarantee that allows the use of receivables as debt collateral in business practices in Indonesia. Receivables bound by fiduciary collateral are deemed special collateral in the context of civil law. Special collateral will be prioritised in case the debtor does not voluntarily make when due. In business practices, long-term receivables will be established following an agreement between a debtor and a third party. The receivables that the debtor is entitled to receive from the third party will be provided as collateral to secure the debtor’s obligations under his loan agreement with the creditor. The issue discussed in this paper is the fact that although theoretically, special collateral in the form of receivables should be able to increase the creditor’s assurance of getting repaid, in practice, long-term receivables put higher risk on the creditor instead. This paper adopts the normative juridical approach, focusing on juridical studies regarding the creditors' risk in the use of receivables, specifically long-term debt collateral. This paper shows that receivables used as collateral in fiduciary agreements put the greatest risk on the creditor, especially if the agreement between the debtor and the third-party stipulates that in case the debtor fails to fulfil his obligations, all receivables that he is supposed to receive from the third party will be aborted and become non-existent.